Linear versus seasonal growth of dairy heifers decreased age at puberty but did not affect first lactation milk production. Issue 1 (2nd January 2021) - Handcock, Rhiannon C.; Jenkinson, Catriona M. C.; Laven, Richard; McNaughton, Lorna R.; Lopez-Villalobos, Nicolas; Back, Penny J.; Hickson, Rebecca E.
ABSTRACT: The aim of this study was to compare conformation, age at puberty and subsequent milk production of Holstein–Friesian–Jersey crossbred heifers grown in a linear trajectory (Target; n = 55) between 6- and 15-month target liveweights (LWT), with heifers grown in a seasonal manner (Seasonal; n = 55) of slow over first winter and fast over spring. Heifers that grew to Target attained puberty 38 days earlier than heifers that grew in a seasonal manner; however, no difference between treatments in the date of first calving occurred. Heifers in the seasonal treatment were 1 cm ( P = .032) taller than those in the target treatment, but similar in girth and length. There was no effect of treatment on first lactation milk production. These results suggest that provided heifers reached their pre-mating target LWT, the growth trajectory between target LWT at 6 and 15 months of age did not negatively impact frame size or first lactation milk production.